Impaired uptake of conjugated bile acids and hepatitis b virus pres1-binding in na+-taurocholate cotransporting polypeptide knockout mice - Slijepcevic, Davor; Kaufman, Christina; Lempp, Florian A.; Mier, Walter; Urban, Stephan (Hepatology, 2015)
The Na+-taurocholate cotransporting polypeptide (NTCP) mediates uptake of conjugated bile acids (BAs) and is localized at the basolateral membrane of hepatocytes. It has recently been recognized as the receptor mediating hepatocyte-specific entry of hepatitis B virus and hepatitis delta virus. Myrcludex B, a peptide inhibitor of hepatitis B virus entry, is assumed to specifically target NTCP. Here, we investigated BA transport and Myrcludex B binding in the first Slc10a1-knockout mouse model (Slc10a1 encodes NTCP). Primary Slc10a1−/− hepatocytes showed absence of sodium-dependent taurocholic acid uptake, whereas sodium-independent taurocholic acid uptake was unchanged. In vivo, this was manifested as a decreased serum BA clearance in all knockout mice. In a subset of mice, NTCP deficiency resulted in markedly elevated total serum BA concentrations, mainly composed of conjugated BAs. The hypercholanemic phenotype was rapidly triggered by a diet supplemented with ursodeoxycholic acid. Biliary BA output remained intact, while fecal BA excretion was reduced in hypercholanemic Slc10a1−/− mice, explained by increased Asbt and Ostα/β expression. These mice further showed reduced Asbt expression in the kidney and increased renal BA excretion. Hepatic uptake of conjugated BAs was potentially affected by down-regulation of OATP1A1 and up-regulation of OATP1A4. Furthermore, sodium-dependent taurocholic acid uptake was inhibited by Myrcludex B in wild-type hepatocytes, while Slc10a1−/− hepatocytes were insensitive to Myrcludex B. Finally, positron emission tomography showed a complete abrogation of hepatic binding of labeled Myrcludex B in Slc10a1-/- mice. Conclusion: The Slc10a1-knockout mouse model supports the central role of NTCP in hepatic uptake of conjugated BAs and hepatitis B virus preS1/Myrcludex B binding in vivo; the NTCP-independent hepatic BA uptake machinery maintains a (slower) enterohepatic circulation of BAs, although it is occasionally insufficient to clear BAs from the circulation. (Hepatology 2015;62:207-219)